Emerging Technologies in Distance Education - George Veletsianoseauthor (Athabasca University Press, 2010)
A one-stop knowledge resource, Emerging Technologies in Distance Education showcases the international work of research scholars and innovative distance education practitioners who use emerging interactive technologies for teaching and learning at a distance. This widely anticipated book harnesses the dispersed knowledge of international experts who highlight pedagogical, organizational, cultural, social, and economic factors that influence the adoption and integration of emerging technologies in distance education. Emerging Technologies in Distance Education provides expert advice on how educators can launch effective and engaging distance education initiatives in response to technological advancements, changing mindsets, and economic and organizational pressures. The volume goes beyond the hype surrounding Web 2.0 technologies and highlights the important issues that researchers and educators need to consider to enhance educational practice.